BOLD responses in human auditory cortex are more closely related to transient MEG responses than to sustained ones - Gutschalk, Alexander; Hämäläinen, Matti; Melcher, Jennifer R. (Journal of neurophysiology, 2010)
Blood oxygen level dependent-functional magnetic resonance imaging (BOLD-fMRI) and magnetoencephalographic (MEG) signals are both coupled to postsynaptic potentials, although their relationship is incompletely understood. Here, the wide range of BOLD-fMRI and MEG responses produced by auditory cortex was exploited to better understand the BOLD-fMRI/MEG relationship. Measurements of BOLD and MEG responses were made in the same subjects using the same stimuli for both modalities. The stimuli, 24-s sequences of click trains, had duty cycles of 2.5, 25, 72, and 100%. For the 2.5% sequence, the BOLD response was elevated throughout the sequence, whereas for 100%, it peaked after sequence onset and offset and showed a diminished elevation in between. On the finer timescale of MEG, responses at 2.5% consisted of a complex of transients, including N1m, to each click train of the sequence, whereas for 100% the only transients occurred at sequence onset and offset between which there was a sustained elevation in the MEG signal (a sustained field). A model that separately estimated the contributions of transient and sustained MEG signals to the BOLD response best fit BOLD measurements when the transient contribution was weighted 8- to 10-fold more than the sustained one. The findings suggest that BOLD responses in the auditory cortex are tightly coupled to the neural activity underlying transient, not sustained, MEG signals.